2010
DOI: 10.1002/pon.1633
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and concerns about ‘returning to work’ for women breast cancer survivors: a literature review

Abstract: Objective: To explore how female breast cancer patients experience work incapacity during the treatment and return-to-work phases and how interactions between patients and stakeholders affect this experience.Method: Database search for full text articles published between January 1995 and January 2008 that focused on employed female breast cancer patients, factors related to work incapacity, and returning to work. Only results based on self-report data were included. Studies focusing on treatment, financial fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
176
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(194 citation statements)
references
References 18 publications
13
176
2
3
Order By: Relevance
“…Several studies found that breast cancer patients often experience difficulties when continuing to work or returning to work after treatment because they had to cope with functional changes, support from co-workers and employers, and job flexibility (Ahn et al, 2009;Tiedtke et al, 2010). Therefore, it would be necessary to develop a tailored intervention program for working breast cancer patients, helping them to manage altered appearance and keep their self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that breast cancer patients often experience difficulties when continuing to work or returning to work after treatment because they had to cope with functional changes, support from co-workers and employers, and job flexibility (Ahn et al, 2009;Tiedtke et al, 2010). Therefore, it would be necessary to develop a tailored intervention program for working breast cancer patients, helping them to manage altered appearance and keep their self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that most employed breast cancer survivors are able to return to work (1-3) but often experience difficulties managing their work, for instance due to physical (eg, arm function) or cognitive work limitations (eg, concentration, fatigue), or unreasonable treatment at the workplace (eg, feelings of being discriminated against, unsupportive work environment) (4)(5)(6). It is important to understand the difficulties cancer survivors experience in order to develop interventions to better support them in their resumption of work.…”
mentioning
confidence: 99%
“…Of the included reviews, thirteen reported challenges faced by bca patients and survivors [27][28][29][30][31][32][33][34][35][36][37][38]40 . Their findings are categorized and described next.…”
Section: Cancer-or Cancer Treatment-related Challengesmentioning
confidence: 99%
“…Three reviews reported fatigue in bca patients and survivors 28,30,38 . According to those reviews, fatigue is one of the most frequently observed side effects during the active treatment period and beyond 28,30 .…”
Section: Fatiguementioning
confidence: 99%
See 1 more Smart Citation